Violent Video Game Playing, Aggression and Wellbeing in Emerging Adulthood (Global Journal of Human-Social Science, 2024)
Purpose This study aimed to explore the relationship between level of violence in video games played problem game playing and engagement in gaming aggression empathy and wellbeing Method This study used an online survey with questionnaire data collection in a sample of 304 emerging adults aged between 18 and 24 years of age 124 males and 180 females Findings The model proposed was supported by the data and suggests that the relationship between violence in games and aggression and empathy is mediated by engagement and addictive tendencies and the impact on wellbeing is largely through aggression and empathy Conclusions We conclude that future research should take cognisance of these mediational factors and consider the developmental stage of participants in order to get a clearer picture of effects
Keywords: violent video games; problem game playing; game engagement; aggression; empathy; wellbeing